Structural awareness for collaborative learning environments - Reyes, Pablo (2006)
In this paper we propose a peer-to-peer support approach that we call structural awareness support. The structural awareness aims to support the communication that takes place in virtual learning communities. Its emphasis is on revealing the group structure to its participants in order to promote collaborative interactions. This support has been implemented on a forum type tool called Mailgroup. It has been tested twice in different contexts, obtaining initial feedback of its pertinence according to our objectives